2018
DOI: 10.1117/1.jbo.23.7.071208
|View full text |Cite
|
Sign up to set email alerts
|

Optical model of the murine lung to optimize pulmonary illumination

Abstract: We describe a Monte Carlo model of the mouse torso to optimize illumination of the mouse lung for fluorescence detection of low levels of pulmonary pathogens, specifically Mycobacterium tuberculosis. After validation of the simulation with an internally illuminated optical phantom, the entire mouse torso was simulated to compare external and internal illumination techniques. Measured optical properties of deflated mouse lungs were scaled to mimic the diffusive properties of inflated lungs in vivo. Using the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The computational model was developed in LightTools Illumination software (Synopsys Inc.), building on our previous illumination model [11]. The model incorporates the anatomy of a small animal with appropriate internal structures and optical properties.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The computational model was developed in LightTools Illumination software (Synopsys Inc.), building on our previous illumination model [11]. The model incorporates the anatomy of a small animal with appropriate internal structures and optical properties.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of source manipulations did not suggest any improvement in fluorescence signal. Simulations of internal illumination showed that a broader divergence angle would result in more effective illumination of the lung [11]. However, this did not reliably translate into a significant improvement in collected fluorescence.…”
Section: Simulated Fluorescence and Spectral Unmixingmentioning
confidence: 97%
See 3 more Smart Citations